Selection of an appropriate fluorescent reference material to assess microplastic recovery in natural waters - Noah A. D’Ascanio; Husein Almuhtaram; Robert C. Andrews (Microplastics and Nanoplastics)
Abstract Monitoring programs have been recently proposed to characterize the presence of microplastics (MPs) in source and treated drinking waters. Successful implementation of such programs will require the development of standardized sampling protocols that can address MP particles < 20 µm, representing the most abundant sizes and relevance in terms of potential human health impacts. Validation of sampling methodologies typically involve spike and recovery trials (to serve as positive controls). To-date, no known methods have been proposed for the production of fluorescent reference materials that are representative of the shape and size distribution of environmental MPs (excluding tire and rubber particles). In this study, an optimal fluorescence reference suspension was developed for use in spike and recovery assessments of microplastic sampling methods when considering source and treated drinking waters. Aqueous particle suspensions were prepared using both commercially available microspheres and lab-prepared MP fragments, such that relative standard deviations (RSD) were calculated within size bins. Nile red-stained polyethylene terephthalate (PET) fragments were identified as an optimal reference material based on an RSD of 2.5% among replicate spikes. No change in fluorescence intensity was observed for Nile red-stained PET fragments following a process to remove extraneous (non-plastic) particles that incorporated a Fenton’s reagent and enzyme-based methodology. In addition, fluorescence intensity of Nile red-stained PET fragments in solution was observed to be stable over a four-month period. As such, it is anticipated that fluorescent PET fragments may be employed in future studies where assessment of microplastic recovery is desired.